Analyzing Social Media Usage and Political Participation Among First-Time Voters in Indonesia’s 2024 Election - Padoma, Orlando; Rahmawati, Dian Eka (Jurnal Review Politik, 2024)
This article aims to analyze Social Media Use as a platform for political participation among first-time voters in Indonesia, particularly for the 2024 election. Social Media Use as a medium of political participation among first-time voters significantly impacts the political process and elections. This research is based on a qualitative method approach using a literature approach. Data collection techniques include documents and library data relevant to the subject matter, such as journal articles, books, Google Scholar, and references from websites accessed via the Internet. The collected data is then analyzed using descriptive techniques, which involve presenting and interpreting the data in detail. The findings reveal that social media significantly influences both the political participation and political awareness of first-time voters. For the 2024 election, according to the results of the DPT determination by the KPU, the number of first-time voters or millennial generation, namely Generation Y and Generation Gen Z aged 17-30 years and have never exercised their right to vote reached 63,953,031 people or 31.23%. First-time voters widely use social media platforms such as Facebook, Twitter, WhatsApp, Instagram, Telegram, and Messenger